2017
DOI: 10.1186/s13068-016-0696-6
|View full text |Cite
|
Sign up to set email alerts
|

The sole introduction of two single-point mutations establishes glycerol utilization in Saccharomyces cerevisiae CEN.PK derivatives

Abstract: BackgroundGlycerol is an abundant by-product of biodiesel production and has several advantages as a substrate in biotechnological applications. Unfortunately, the popular production host Saccharomyces cerevisiae can barely metabolize glycerol by nature.ResultsIn this study, two evolved derivatives of the strain CEN.PK113-1A were created that were able to grow in synthetic glycerol medium (strains PW-1 and PW-2). Their growth performances on glycerol were compared with that of the previously published evolved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 62 publications
(81 reference statements)
2
21
0
Order By: Relevance
“…During the fermentation process, a significant accumulation of glycerol was also found at about 5 g/L in glucose consumption stage. Ho and colleagues reported both UBR2 and GUT1 with single point mutation could be regarded as targets for establishing glycerol utilization in strains of the CEN.PK family (Ho et al, 2017). It was also found that regulatory and metabolic trade-offs of glycerol utilization in S. cerevisiae were revealed by laboratory evolution, which could guide us to enhance glycerol consumption rationally in our study (Strucko et al, 2018).…”
Section: Dhaa Enrichment By 5 L Fed-batch Fermentationsupporting
confidence: 56%
“…During the fermentation process, a significant accumulation of glycerol was also found at about 5 g/L in glucose consumption stage. Ho and colleagues reported both UBR2 and GUT1 with single point mutation could be regarded as targets for establishing glycerol utilization in strains of the CEN.PK family (Ho et al, 2017). It was also found that regulatory and metabolic trade-offs of glycerol utilization in S. cerevisiae were revealed by laboratory evolution, which could guide us to enhance glycerol consumption rationally in our study (Strucko et al, 2018).…”
Section: Dhaa Enrichment By 5 L Fed-batch Fermentationsupporting
confidence: 56%
“…3B ), likely due to the poor utilization of glycerol by BY4741. Suspecting slow glycerol utilization to be limiting to growth, we transferred the pRJP1444 plasmid into a strain optimized for glycerol utilization (CEN.PK113-1A-GUT1 JL1 UBR2 CBS 34 ), yielding strain yRJP224, and assayed for growth on d -galUA media. Excitingly, we observed higher saturating densities for yRJP224 in d -galUA media compared to our precursor strains and yRJP223, a wild-type CEN.PK strain expressing the catabolic pathway (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As the E. magnusii culture is a classic aerobe, it has a complete respiratory chain with invariable couple point I and well-developed mitochondria. Glucose is not as suitable substrate for the species as the respiratory substrates of glycerol, lactate, and ethanol, which in turn are not the preferred carbon sources for the classic fermentative yeast of S. cerevisiae [36,37].…”
Section: Discussionmentioning
confidence: 99%